Effect of Budgeting and Financial Awareness on Sustainability of Small and Medium Enterprises in South Africa during the COVID-19 Era: Array - Olarewaju, Odunayo; Msomi, Thabiso (The Journal of Accounting and Management, 2021)
Budgeting is universal and can be implemented in all industries, SMEs inclusive, as it has the sole purpose of meeting corporate targets. The objective of this study is to examine the effect of budgeting and financial awareness on sustainability of small medium enterprises. The quantitative research method was adopted for this study and the purposive sampling technique was chosen to select the participants for this study. The study collected primary data from respondents who are owners of SMEs in the retail, construction, manufacturing sectors, etc and the data was analysed using SPSS. A total of 310 research questionnaires was administered and 304 research questionnaires were returned for analysis (giving a 98% response rate). A regression analysis and Pearson’s correlation analysis were conducted. The outcome of Pearson’s correlation shows moderate correlation (r value is 0.372) between budgeting, financial awareness and sustainable SMEs. There is also a significant effect of budgeting and financial awareness on sustainability as revealed in p-value <0.0005. Budgeting plays an important role in SME sustainability more than financial awareness as budgeting uniquely accounts for the largest proportion of the variance in the regression model. This implies that SMEs should give more attention to budgeting to ensure their sustainability such that more training or awareness is given to forecasting and financial planning.